Venous Complications of Pancreatitis: A Review - Aswani, Yashant; Hira, Priya (JOP. Journal of the Pancreas, 2015)
Pancreatitis is notorious to cause vascular complications. While arterial complications include pseudoaneurysm formation with a propensity to bleed, venous complications can be quite myriad. Venous involvement in pancreatitis often presents with thrombosis. From time to time case reports and series of unusual venous complications associated with pancreatitis have, however, been described. In this article, we review multitudinous venous complications in the setting of pancreatitis and propose a system to classify pancreatitis associated venous complications. Image: Dilated venous channels in the wall of gallbladder at sonogram.